Peran Institutional Ownership dalam Memoderasi Return on Asset dan Net Profit Margin terhadap Firm Value - Luthfi, Muhammad Farisan; Rahman, Syarif Syahrul; Noviriani, Eliza; Fiermeiza, Naufal Aulia (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study aims to examine the influence of Return on Assets (ROA) and Net Profit Margin (NPM) on Firm Value, as well as the moderating role of Institutional Ownership. Firm Value is a crucial indicator reflecting market perception of a company’s performance and future prospects, with profitability and corporate governance being key influencing factors. ROA and NPM were used as measurement of profitability, while Institutional Ownership was considered as an external monitoring mechanism that plays an important role in corporate governance. A quantitative approach is employed using secondary data from 23 companies consistently listed in the LQ45 index during 2018–2022, resulting in 115 firm-year observations. Data analysis was conducted using a fixed effect regression model and moderated regression analysis (MRA), processed with EViews 10. The results showed that ROA had a significant positive effect on Firm Value, while NPM did not have any significant effect. Additionally, Institutional Ownership strengthened the relationship between ROA and Firm Value but weakens the influence of NPM on Firm Value. These findings indicated that institutional investors play an effective supervisory role in optimizing asset management, although they may restrict managerial flexibility in short-term profitability strategies.